Bio-agent based module for integrated management of sheath blight (Rhizoctonia solani) of rice - DUBEY, S C; TRIPATHI, ARADHIKA; INDIRA, S (The Indian Journal of Agricultural Sciences, 2019)
Rice (Oryza sativa L.) is an important cereal crop consumed worldwide and sheath blight caused by Rhizoctonia solani Künh is one of the limiting factors for its sustainable production. The experiments were conducted during rainy seasons of 2013 and 2014 to evaluate the performance of various treatments comprising bio-formulation Pusa 5SD prepared from Trichoderma viride (IBSD T20) and T. virens (IARI P3), liquid formulation of Bacillus subtilis (IBSD), fungicides hexaconazole and carbendazim + thiram by various methods of applications (seed treatment and foliar spray) to develop an effective module for the integrated management of the disease. Twenty treatments consisting of four levels of seed treatments and five levels of foliar spray including control for each factor were evaluated. A combination of seed treatment and foliar spray with T. virens (IARI P3) based Pusa 5SD provided the highest number of hills, tillers, plant height, number of grains, plant dry weight and grain yield along with the lowest relative lesion height and disease index. Whereas, the highest seed germination was recorded in a combination of seed treatment and foliar spray of T. viride (IBSD T20) based Pusa 5SD. A combination of seed treatment with T. virens (Pusa 5SD) and foliar spray of liquid formulation of B. subtilis (IBSD) was the next effective treatment for increasing the grain yield and yield attributing parameters and decreasing the disease. The module developed in the present study is suitable for management of the disease.